Extrajudicial Killing dalam Kebijakan War on Drugs di Filipina Ditinjau dari Hukum Pidana Internasional - Salasmita, Salasmita; Putra Kurnia, Mahendra; Erawaty, Rika (Fakultas Hukum Universitas Mulawarman, 2022)
The threat of drug abuse in the Philippines has prompted President Rodrigo Duterte to intensify a campaign to combat it, through the War on Drugs, a program to neutralize drug abusers. However, the implementation of the policy is allegedly loaded with serious human rights violations in the form of extrajudicial killings committed against civil society. This research aims to analyze whether extrajudicial killings carried out in the War on Drugs Policy during the administration of President Duterte were qualified as gross human rights violations and the application of international court jurisdiction over the situation. The research method used in this research is doctrinal research. The results showed that extrajudicial killings in the Philippines met the elements of crimes against humanity so that they could qualify as gross violation of human rights. The International Community has rightly sought to enforce the law on this situation through the International Criminal Court with President Duterte as the individual who must be held responsible.